Six Principles Energy Conservation Techniques for Respiratory Frequency and Oxygen Saturation in Chronic Obstructive Pulmonary Disease Patients - Suksi Riani; Michella Putri Pohaci; Mugi Hartoyo (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2023)
Background: Chronic obstructive pulmonary disease refers to chronic diseases, such as emphysema, chronic bronchitis, asthma, or a combination of them. The observed symptoms of chronic obstructive pulmonary disease include breathlessness, wheezing, repeated respiratory tract infection, losing weight, and prolonged fatigue. Objectives: This research determined the influence of a 6-principle energy conservation technique on the respiratory frequency and oxygen saturation of Chronic Obstructive Pulmonary Disease (COPD) patients. Methods: This quasi-experimental research applied one group pretest-posttest design. The research design was useful to measure the respiratory rate and oxygen saturation before and after the implementation of 6-principle energy conservation. The researcher involved 29 respondents taken by accidental sampling. Results: The result showed the frequency mean before the intervention was 26.34 times per minute and after the intervention was 23.83 times per minute. The oxygen saturation, SpO2, before the intervention, was 97.17% while after the intervention was 96.76%. The Wilcoxon test found the influence of a 6-principle energy conservation technique toward the respiratory rate, a p-value of 0.000. On the other hand, the researcher did not find the influence of the 6-principle energy conservation technique on the COPD patient (p-value 0.944). Conclusion: The researcher recommends the implementation of 6-principle energy conservation as the non-pharmacological intervention alternative to manage the abnormal respiratory rate of COPD patients.